Assessing customer-based brand equity in predicting customers’ repurchase intention in family restaurant / Mohd Aliff Abdul Majid - Abdul Majid, Mohd Aliff (2013)
Brand equity has become a very important factor that influences consumer’s perceptions of a brand, regardless of industry. This study applied four of five Aaker’s components of brand equity i.e. brand loyalty, perceived quality, brand awareness and brand associations that defined as customer-based brand equity (CBBE). The main objective of this study was to investigate the relationships between four dimensions of CBBE and repurchase intention towards family restaurants in Klang Valley. Total of 450 questionnaires were distributed to customers at the participating restaurants and 349 usable questionnaires were analyzed. The results showed that only brand loyalty and brand association had significant relationships (p<.001) towards repurchase intention and brand association was found to be the strongest determinant (β=.55) on repurchase intention. Furthermore, the findings established that perceived quality was the most important component in how customer perceived CBBE in family restaurant. The findings also established that The Chicken Rice Shop obtained the highest total brand equity in relative to other restaurants.